A CORAGEM DE SER DE PAUL TILLICH E A VIA CRUCIS DO CORPO DE CLARICE LISPECTOR: Semelhanças e assimetrias em busca de uma leitura teológico-existencial da obra de Lispector - Tada, Elton Vinicius Sadao (2010)
The present work search to do a theological reading of literature, in the specific case of the book ―The via crucis of the body of Clarice Lispector. The theological presupposition that is used to do this analysis is the one of Paul Tillich s theology, parting from his theology of culture and from his concept of courage to be. To this project was necessary to follow some steps, and the first one is retract the discussion about what is and how should be one research that include theology and literature. In the second place was exposed biographical narratives about Clarice Lispector and Paul Tillich that could bring light to the thematic. Subsequently the book ―The via crucis of the body was presented within the general work of Clarice Lispector, and the basic theoretical points of Paul Tillich s theology used in the work was discussed. In the last step, the studded theology of Paul Tillich was applied in the stories of the book ―The via crucis of the body appearing as a result a theologicalexistential reading of the book, and proposing an existential way to analysis the literature.